Integrated Portable Vein Measurement Device - Khor Gin Haur; Khor Wan Yi; Siti Zulaikha Zaini; Suhana Abdul Rahim; Ali Saleh Ba Wazir; Nur Farahiyah Mohammad; Nashrul Fazli Mohd Nasir (Multidisciplinary Applied Research and Innovation, 2021)
The main goal of this project is to develop a low cost, non-invasive and portable vein measurement device. The parameter indicated in this project is the size of the vein. Vein mapping is performed first with near infrared (NIR) to visualize the vein under human arm. A Raspberry Pi No infrared (NoIR) camera is used to capture the image of the vein. A graphical user interface (GUI) is created for vein image processing and vein size measurement. Internet of things (IoT) is applied to store the edited image and patient data in the cloud. Mobile application is created for medical personnel and doctors as consultant and monitoring purpose. This system increases the accuracy of vein size measurement and evaluation, thus minimize the human error made by the medical personnel.